Tingkat kesegaran bunga Gladiol (Gladiolus hybridus Hort.) potong dalam rendaman campuran air kelapa hijau dan natrium hipoklorit - Titik Dwi Lidiyanti; Endah Dwi Hastuti; Munifatul Izzati (Jurnal Biologi Tropika, 2020)
Gladiolus hybridus Hort. is one of the cut flower commodities that is much demanded by peope since they have a variety of colors. The freshness of the flower that has been separated from the old parent plants will be decreased. Coconut water contains mineral, sugar, vitamin, and fitohormon that can keep its freshness. Sodium hypochlorite (NaClO) is a disinfectant that can inhibit the growth of microorganisms. This research aims to find out the level of the cut flower's freshness that was soaked in the green coconut water and sodium hypochlorite with a different concentration. This research uses Complete Random Design (CRD) with 4x2 factorial. The first factor is the concentration of the green coconut water: 20%, 40%, and 60%. The second factor is the concentration of sodium hypochlorite: 0% and 5%. Each treatment with 3 repetitions. Data is analyzed with Analysis of Variance (ANOVA) proceed with DMRT test at a test level significance of 5%. The results showed that there was an interaction between the mixture of coconut water and sodium hypochlorite on the freshness of the cut Gladiolus flower, the interaction between coconut water 40% and sodium hypochlorite 5% gave optimal results on the freshness of cut flowers. Gladiolus was shown by the results of 4.7 days freshness of freshness, the percentage of the flowering of 10.22%, and the percentage of flower loss of 5.88%.